1974
DOI: 10.1007/bf00439020
|View full text |Cite
|
Sign up to set email alerts
|

Studies of malformation syndromes of man XXXIII: The FG syndrome. An X-linked recessive syndrome of multiple congenital anomalies and mental retardation

Abstract: Abstract. Three brothers and two of their male first cousins were affected with a previously apparently undefined multiple congenital anomaly, mental retardation syndrome which was designated the FG syndrome and which consists of variable growth problems with a disproportionately large head, characteristic appearance and minor anomalies, imperforate anus, mild to severe mental retardation and congenital hypotonia; pylorie stenosis, hypoplastic left heart, generalized dilatation of the urinary tract, cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
2

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 10 publications
2
118
0
2
Order By: Relevance
“…The Opitz-Kaveggia and Lujan syndromes have overlapping (mental retardation, macrocephaly) and also specific (imperforate anus in Opitz-Kaveggia, craniofacial abnormalities in Lujan) manifestations (Opitz and Kaveggia, 1974;Risheg et al, 2007;Schwartz et al, 2007). These symptoms also implicate Med12 as a subunit with gene-specific functions within the Mediator.…”
Section: Med12mentioning
confidence: 99%
“…The Opitz-Kaveggia and Lujan syndromes have overlapping (mental retardation, macrocephaly) and also specific (imperforate anus in Opitz-Kaveggia, craniofacial abnormalities in Lujan) manifestations (Opitz and Kaveggia, 1974;Risheg et al, 2007;Schwartz et al, 2007). These symptoms also implicate Med12 as a subunit with gene-specific functions within the Mediator.…”
Section: Med12mentioning
confidence: 99%
“…In 2007, Risheg found that there are frequent mutations in the twenty-fi rst exon of MED12 of FG syndrome patients, which results in C2881T and R961W mutations in the protein. Thereafter, the relationship between FG syndrome and mutations in MED12 was confi rmed by several other groups (Opitz and Kaveggia, 1974;Risheg et al, 2007;Graham et al, 2008;Graham et al, 2010). In addition, Rump P and colleagues found that three cousins suffering from FG syndrome all bear a mutation (G958E) in MED12, suggesting that the G958E mutation may also cause FG syndrome (Rump et al, 2011).…”
Section: Med12 Mutation and The X-linked Mental Retardationmentioning
confidence: 91%
“…FG syndrome, also called Opitz-Kaveggia syndrome, was fi rst reported by OpitzKaveggia in 1974 (Opitz andKaveggia, 1974). It is an X chromosome-associated genetic disease.…”
Section: Med12 Mutation and The X-linked Mental Retardationmentioning
confidence: 99%
“…L'agéné^i du corps calleux, partielle ou complète, comme symptôme ou comme maladie a été mise en relation avec plusieurs modes de transmission: lié au sexe (Menkes et al, 1964;Opitz et Kaveggia, 1974), autosomal dominant (Lynn et al, 1980) et autosomal récessif (Shapira et Cohen, 1973;Ozdirim et Renda, 1978). On doit signaler le syndrome d'Aicardi (Aicardi et al, 1965) qui pourrait s'avérer multifactoriel avec une "préférence" pour les femmes (Aicardi et al, 1969;Dennis et Bower, 1972;De Jong et al, 1976).…”
Section: Agénésie Du Corps Calleux Et Héréditéunclassified